Functional epitope analysis of the human CD4 molecule: antibodies that inhibit human immunodeficiency virus type 1 gene expression bind to the immunoglobulin CDR3-like region of CD4. - Benkirane, M (1995)
We recently demonstrated that monoclonal antibody (MAb) 13B8-2, specific for the immunoglobulin (Ig) complementary determining region 3 (CDR3)-like region of the CD4 molecule, inhibits viral transcription in human immunodeficiency virus (HIV)-infected CEM cells and HIV type 1 (HIV-1) promoter activity. Here, we have studied the capacity of several MAb specific for the D1 domain of CD4, including anti-CDR2-like (Leu-3a and ST4) and anti-CDR3-like (13B8-2 and ST40) MAb, and for the D2 domain of CD4 (BL4) to inhibit both provirus transcription in HIV-1LAI-infected CEM cells and transcription of the chloramphenicol acetyltransferase (CAT) gene under control of the HIV-1 long terminal repeat in transiently transfected CEM cells. We found that HIV-1 promoter activity and provirus transcription are inhibited only by MAb that bind to the CDR3-like region in domain 1 of CD4. Moreover, we demonstrated that the Fab fragment of an anti-CDR3-like region-specific anti-CD4 MAb is a powerful inhibitor of HIV-1 promoter activity. These results have implications for understanding the role of the CDR3-like region in CD4 T-cell signaling, which controls provirus transcription.